Relationship between Metacognitive Experiences and Self-efficacy, Skill, andDifficulty of Mathematical Taskcacy, skill, and difficulty of mathematical task - Alfaro-Barquero, Alejandra (2026)
Objective. This study aimed to evaluate the relationship between self-efficacy, ability, and task difficulty in mathematics, and the metacognitive accuracy of performance judgments and academic achievements using structural equation modeling. Method. A non-experimental quantitative study was conducted in 2012 with 495 university students. The study used the self-efficacy scale from the MSLQ, mathematics scores from the Tecnológico de Costa Rica admission exam and the enrolled course, a test of mathematical exercises, as well as self-reported performance judgments. Results. Evidence found supports the positive effect of mathematical ability and self-efficacy on metacognitive accuracy, and an inverse relationship with item difficulty. No association was found between metacognitive accuracy and academic achievement